Hunger and Food Sovereignty among the Kaiowa and Guaraní in Brazil - Heusi Silveira, Nádia (2020)
Over the last 70 years, the Kaiowa and Guarani peoples living in Brazil have suffered massive loss of their traditional territories. Examining the case of the Caarapó Indigenous Land, the article argues that territorial expropriation, along with the public policies that promoted it, led to significant and disruptive social and environmental changes for the Kaiowa and Guarani and has compromised their food sovereignty. It demonstrates that the rituals of the past related to agricultural production were events that produced extended reciprocity between kin groups and abundance of food for all. It is concluded that the State's actions taken to resolve the current situation and to guarantee food and nutritional security of these peoples, have been partial and disappointing.